Comparative oviposition preferences of Aedes (Stegomyia) aegypti (L.) to water from storm water drains and seasoned tap water - Chen, C.D.; Nazni, W.A.; Seleena, B.; Moo, J.Y.; Azizah, M.; Lee, H.L. (2007)
The comparative oviposition preferences of Aedes aegpti to water from storm-water drains and seasoned tap water were evaluated in the laboratory. The sample was collected from concrete storm-water drains with stagnant clear water in a dengue-endemic site, Taman Samudera, Selangor. Ae. aegypti adults were given a blood meal and released into the caged. Gravid females were given a choice between drain water and seasoned tap water for egg deposition. In a no-choice test, there was no significant difference in the numbers of eggs, larvae, pupae and adults colonized from the drain water and seasoned tap water (p>0.05), indicating that Ae. aegypti oviposit their eggs on a substrate which is readily available. In a choice test, the number of eggs laid by Ae. aegypti in drain water (1630.67 ± 204.26) was significantly more than that in seasoned tap water (221.33 ± 53.18) (p<0.05). The number of eggs was 6-fold higher in the drain water compared to seasoned tap water. The oviposition activity index was 0.71, indicating that the drain water was more attractive compared to seasoned tap water as an oviposition substrate. The pH and biochemical oxygen demand (BOD) values of both drain water and seasoned tap water were not significantly different (p>0.05), indicating that water from the drain did not contain high organic content. Significant water conductivity (p<0.05) and the presence of bacteria could have contributed to the site selection for egg laying by Ae. aegypti. The drain water successfully supported the colonization of the immatures, with the emergence of 824.33 ± 13.96 adult mosquitoes. The ratio of male and female mosquitoes was 1:1. This study concluded that the concrete drainage system with clear stagnant water provides a suitable medium for the colonization of dengue vector Ae. aegypti.